2006
DOI: 10.1002/mus.20646
|View full text |Cite
|
Sign up to set email alerts
|

Weekly oral prednisolone improves survival and strength in male mdx mice

Abstract: Although corticosteroids alleviate weakness in mdx mice, no long-term treatment has determined whether this benefit is maintained. We studied mdx mice forelimb grip strength and fatigue from 3 through 84 weeks and followed survival through 104 weeks. The mdx mice were given twice weekly oral prednisolone (5 mg/kg) beginning at 3 or 4 weeks. Treated mdx mice survived longer than untreated mice. Between 3 and 10 weeks, treated and untreated mdx mice had similar strength. Between 10 and 24 weeks, strength and str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
47
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(62 citation statements)
references
References 31 publications
12
47
0
1
Order By: Relevance
“…3 E and F). Importantly, single-mutant intercrosses of mice harboring either the null Klf15 allele or the mdx allele alone do not produce such mortality or muscle damage (23,49). Our observations in these compound mutant strains support the contention that there is a genetic interaction between KLF15 deficiency and the dystrophic pathology of the mdx mouse model.…”
Section: Klf15 Issupporting
confidence: 76%
See 1 more Smart Citation
“…3 E and F). Importantly, single-mutant intercrosses of mice harboring either the null Klf15 allele or the mdx allele alone do not produce such mortality or muscle damage (23,49). Our observations in these compound mutant strains support the contention that there is a genetic interaction between KLF15 deficiency and the dystrophic pathology of the mdx mouse model.…”
Section: Klf15 Issupporting
confidence: 76%
“…We subjected male Klf15 +/− mdx mice and Klf15 +/+ mdx littermate controls to a therapeutic trial of prednisolone using a low and intermittent dosing regimen similar to that used clinically in DMD patients and in prior studies of mdx mice (Fig. 3G) (15,19,49). We confirmed that this regimen of chronic prednisolone produced the expected increase in muscle KLF15 and its downstream targets in Klf15 +/+ mdx control mice, with blunted expression in Klf15 +/− mdx mice ( Fig.…”
Section: Klf15 Ismentioning
confidence: 99%
“…Studies of prednisone administration in children with DMD have suggested that weekend dosing has comparable beneficial effects compared with daily dosing (34). In the mdx model, weekly dosing was associated with a sustained long-term benefit compared with that in control-treated mice (35). However, there has been limited widespread uptake of weekly steroid regimens, so we investigated the effects of weekly and daily steroid dosing in an animal model of muscular dystrophy.…”
Section: Resultsmentioning
confidence: 99%
“…9 The mdx mice continued to weigh more than wild-type mice at 38 – 40 weeks of age, but the difference was not significant. Keeling et al 27 reported a 15% increase in mdx body weights compared with wild-type from 10–12 weeks until 48–52 weeks. However, this was found in sedentary mdx mice, and our weights were a few grams less, possibly related to our exercise protocol.…”
Section: Discussionmentioning
confidence: 99%